2021
DOI: 10.3390/polym13142299
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Collagen and Gelatin-Based Cryogels: Fabrication, Classification, Properties and Biomedical Applications

Abstract: Decades of research into cryogels have resulted in the development of many types of cryogels for various applications. Collagen and gelatin possess nontoxicity, intrinsic gel-forming ability and physicochemical properties, and excellent biocompatibility and biodegradability, making them very desirable candidates for the fabrication of cryogels. Collagen-based cryogels (CBCs) and gelatin-based cryogels (GBCs) have been successfully applied as three-dimensional substrates for cell culture and have shown promise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 166 publications
1
23
0
2
Order By: Relevance
“…These results also agree with Neres Santos et al [ 55 ] who reported that an increase in freeze-thawing cycles led to less porosity. That mechanism was also found in the forming of collagen and gelatin-based cryogel prepared by the freeze-thawing method [ 56 ]. The helical structure was the main structure of agarose gelation due to its hydrogen bonding and electrostatic interaction [ 57 ].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results also agree with Neres Santos et al [ 55 ] who reported that an increase in freeze-thawing cycles led to less porosity. That mechanism was also found in the forming of collagen and gelatin-based cryogel prepared by the freeze-thawing method [ 56 ]. The helical structure was the main structure of agarose gelation due to its hydrogen bonding and electrostatic interaction [ 57 ].…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, the swelling ratio and protein release of those scaffolds were lower than the swelling ratio and protein release of scaffolds prepared using only the D method. This property may be applied in the development of further material as a controlled drug release scaffold, such as controlling active agent release and cell delivery [ 56 , 58 ]. However, the tensile strength and Young’s modulus of scaffolds prepared by the TD method were lower than those prepared by the D method, without significant difference in elongation.…”
Section: Discussionmentioning
confidence: 99%
“…29 But gelatin, which has a high structural similarity to collagen, is one of the best alternatives to them, as cells have a high tendency to attach to it, which can well maintain them at its surface, as well as produce nanofibrous scaffolds. 30 However, in order to be able to show a good structural feature in the body temperature conditions, it is better to be under a suitable cross linking. 31 Gelatin, on the other hand, is very readily available and easy to extract from animal tissues such as ECM, cartilage and bone.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the polymers naturally present in the ECM, such as collagen, elastin, fibronectin, and hyaluronic acid, have low solubility, and the resulting solutions have poor viscoelastic properties 29 . But gelatin, which has a high structural similarity to collagen, is one of the best alternatives to them, as cells have a high tendency to attach to it, which can well maintain them at its surface, as well as produce nanofibrous scaffolds 30 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the multitude of work on cryogels, we would like to highlight here the major fields of application and the specific advantages of GAG-based cryogels as scaffolds in cell cultivation and tissue engineering. It should be mentioned that in numerous described applications, composite cryogels made of GAG components with protein-based materials are used [ 98 , 99 , 100 ].…”
Section: Applications Of Gag-based Cryogels As Scaffolds In Cell Culture and Tissue Engineeringmentioning
confidence: 99%